Analisis Implementasi dan Keberlanjutan Bisnis Carbonoffee di Kota Palembang - Leven Winata; Jovan Fernando; Megawati Megawati (Universitas Multi Data Palembang, 2026)
This research aims to analyze the sustainability and development of the Carbonoffee business as an innovative coffee beverage product that integrates the concepts of sustainability, product innovation, and modern business strategies to increase competitiveness in the market. Initially, this business was an idea by mixing two main raw materials, namely coffee and soda, but over time this business has an innovation: coffee and cendol. This research area focuses on marketing strategy analysis, analysis of business results from financial reports, and analysis of the business's ability to survive long-term. Based on the results of the analysis obtained, it can be concluded that the Carbonoffee business can be run well and sustainably.